Learning from Past Policy: Assessing United States Foreign Policy over Indonesia in Resolving the 1999 East Timor Crisis - Nugroho, Sigit S. (UI Scholars Hub, 2021)
Assessing the output of past foreign policy is instrumental for any country to learn policy-relevant insights, to appreciate its experience, and to improve its future conduct. To glean such insights, this article borrows Baldwin’s framework in assessing the success and failure in foreign policy. Using a case study analysis, it assesses the United States’ (U.S.) influence attempt towards Indonesia to resolve the 1999 East Timor humanitarian crisis. President Clinton’s decision to undergo an influence attempt primarily aimed to change Indonesia’s policy while gaining support from U.S. allies in the process. The article finds that Clinton’s decision was a highly successful attempt. This finding is based on several factors: (1) the attempt effectively attained the intended primary and secondary goals at a considerably high degree; (2) it was conducted at a considerably low cost for the U.S.; (3) it inflicted a high cost towards Indonesia; (4) the increase in Clinton’s stake strengthened the U.S. resolve to pursue the influence attempt; and (5) Clinton had successfully overcome the difficult undertaking as Indonesia possessed higher stake over East Timor. These findings provide some lessons for both U.S. and Indonesian foreign policymakers to chart future relations for the two nations.